2017
DOI: 10.1108/jamr-11-2016-0092
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study into the effectiveness of the HPO Framework

Abstract: Purpose The academic and management literature offers an abundance of techniques for helping organizations improve their performance. Generally, though, these techniques have not been subjected to rigorous, evidence-based evaluation or have been tested in practice over time. The purpose of this paper is to describe a longitudinal study into the effectiveness of the High Performance Organization (HPO) Framework at a social care and rehabilitation organization. Design/methodology/approach The HPO Framework was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…(2) exploring a phenomenon to determine what is happening, that is, seeking to identify connections between events and processes over time; (3) explaining a phenomenon, to seek causal explanations of events and processes as they change over time; and (4) improving the phenomenon, that is, looking for ways to improve some aspect of the phenomenon under study. As the present study aims to explore KIX's sustainable water management over the period 2002-2016, it utilized the second type of longitudinal study approach as it sought to determine what was happening with the airport's sustainable water usage and systems [48].…”
Section: Methodsmentioning
confidence: 99%
“…(2) exploring a phenomenon to determine what is happening, that is, seeking to identify connections between events and processes over time; (3) explaining a phenomenon, to seek causal explanations of events and processes as they change over time; and (4) improving the phenomenon, that is, looking for ways to improve some aspect of the phenomenon under study. As the present study aims to explore KIX's sustainable water management over the period 2002-2016, it utilized the second type of longitudinal study approach as it sought to determine what was happening with the airport's sustainable water usage and systems [48].…”
Section: Methodsmentioning
confidence: 99%
“…Regarding this framework [24] state, based on an extensive literature review, that "across the HPO literature, we found only the HPO framework developed by de Waal as an example of scienti cally validated conceptualization of HPO." In addition, this framework has been extensively tested [25] and applied in the healthcare [23]. We therefore decided to use the HPO framework in our study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There was only one literature source, [23], that was holistic and longitudinal of nature, and contained a framework which healthcare institutions can use in their transformation to a higher quality level. Regarding this framework [24] state, based on an extensive literature review, that "across the HPO literature, we found only the HPO framework developed by de Waal as an example of scienti cally validated conceptualization of HPO."…”
Section: Literature Reviewmentioning
confidence: 99%
“…These studies showed that: the framework is applicable in different cultural settings (de Waal and Frijns, 2009; de Waal et al , 2014a, 2014b. Honyenuga et al , 2014; de Waal et al , 2016; de Waal and Wang, 2017); there is causality between using the HPO framework and achieving increased organisational performance (de Waal and Goedegebuure, 2017); and organisations that apply it in a disciplined manner are indeed able to increase their performance (de Waal and Chachage, 2011; de Waal et al , 2015; de Waal, 2017a, 2017b; de Waal and Mulimbika, 2017; de Waal and de Haas, 2018). …”
Section: The High-performance Organisation Frameworkmentioning
confidence: 99%
“…organisations that apply it in a disciplined manner are indeed able to increase their performance (de Waal and Chachage, 2011; de Waal et al , 2015; de Waal, 2017a, 2017b; de Waal and Mulimbika, 2017; de Waal and de Haas, 2018).…”
Section: The High-performance Organisation Frameworkmentioning
confidence: 99%